Odpowiedź :
Zapisz w postaci sumy algebraicznej :
a) (2x - 4xy) : 2 = x-2xy
b) (6a - 9ab + 1) : (-3) = -2a+3ab-1/3
c) (2x² - 4x - 10) : 2/3 = 3x²-6x-15
d) 10a + 5b - 15 : -5 = 10a+5b+3
e) 8x² - x +36 : 4 = 8x²-x+9
Zapisz w postaci sumy algebraicznej :
a) 3x(x-7) = 3x²-21x
b) a² (a+2b-1) = a³+2a²b-a²
c) -3xy(x+y-3) = -3x²y-3xy²+9xy
a) (2x - 4xy) : 2 = x-2xy
b) (6a - 9ab + 1) : (-3) = -2a+3ab-1/3
c) (2x² - 4x - 10) : 2/3 = 3x²-6x-15
d) 10a + 5b - 15 : -5 = 10a+5b+3
e) 8x² - x +36 : 4 = 8x²-x+9
Zapisz w postaci sumy algebraicznej :
a) 3x(x-7) = 3x²-21x
b) a² (a+2b-1) = a³+2a²b-a²
c) -3xy(x+y-3) = -3x²y-3xy²+9xy
a) (2x - 4xy) : 2 = x - 2 x y
b) (6a - 9ab + 1) : (-3) = -2a + 3ab - 1/3
c) (2x² - 4x - 10) : /dwie trzecie/ = 3x² - 6x - 15
d) 10a + 5b - 15 : -5 = 10a + 5b + 3
e) 8x² - x +36 : 4 = 8x² - x + 9
a) 3x(x-7) = 3x² - 21x
b) a²(a+2b-1) = a³ + 2a²b - a²
c) -3xy(x+y-3) = -3x²y - 3xy² + 9xy
Pozdro))
b) (6a - 9ab + 1) : (-3) = -2a + 3ab - 1/3
c) (2x² - 4x - 10) : /dwie trzecie/ = 3x² - 6x - 15
d) 10a + 5b - 15 : -5 = 10a + 5b + 3
e) 8x² - x +36 : 4 = 8x² - x + 9
a) 3x(x-7) = 3x² - 21x
b) a²(a+2b-1) = a³ + 2a²b - a²
c) -3xy(x+y-3) = -3x²y - 3xy² + 9xy
Pozdro))
a)(2x-4xy):2=x-2xy
b)(6a-9ab+1):(-3)=-2a+3ab-3
c)(2x²-4x-10):2/3=3x²-6x-15
d)10a+5b-15:(-5)=10a+5b+3
e)8x²-x+36:4=8x²-x+9
2.a)3x(x-7)=3x²-21
b)a²(a+2b-1)=a³+2ba²-a²
c)-3xy(x+y-3)=-3x²y-3xy²+9xy
b)(6a-9ab+1):(-3)=-2a+3ab-3
c)(2x²-4x-10):2/3=3x²-6x-15
d)10a+5b-15:(-5)=10a+5b+3
e)8x²-x+36:4=8x²-x+9
2.a)3x(x-7)=3x²-21
b)a²(a+2b-1)=a³+2ba²-a²
c)-3xy(x+y-3)=-3x²y-3xy²+9xy